RESEARCH OF THE NUTRITIONAL STATUS OF DIFFERENT SPECIALTIES SPORTSMAN-ACROBATS - Pastukhova V. A.; Pastukhova A. I.; Tarnavskyi V. O. (Вісник проблем біології і медицини, 2022)
Acrobatic gymnastics is a kind of sport that requires significant coordination skills, physical exertion and optimal diet to achieve the set goals. Therefore, the main purpose of this study was to optimize the nutritional status of acrobats and to detect violations in it early for correction and avoidance of undesirable consequences in advance. To perform this task, a group of acrobats was observed using such methods as the determination of daily and individual energy expenditure of the subjects, the study of the actual nutrition of athletes, the study of blood and urine indicators by biochemical methods. Analyzing the energy value and chemical composition of actual food rations, quantitative and qualitative violations were noted. The caloric content of the daily ration of female athletes is much lower than the average daily energy expenditure. There is violation of the optimal ratio between proteins, fats and carbohydrates in the diet of all studied groups. In the diet of acrobats performing the function of «middle» and «lower» there is a pronounced deficiency of proteins and complex carbohydrates with an excess of fats, mono- and disaccharides, while in the chemical composition of the diets of «upper» acrobats more significant indicators are observed deficiency of all analyzed food components. During the analysis of urea and creatinine concentration indicators in the urine of acrobats, changes were observed compared to the norm. Such indicators of metabolic status are the result of intense physical exertion, mainly anaerobic and glycolytic. Оrganizing the rational nutrition of highly qualified acrobats, an individual approach is necessary, taking into account the specific specialization, the energy orientation of the load and the stage of the training cycle. Thus, by regulating the caloric content and balance of food according to the main and essential ingredients, it is possible to influence the metabolic background of the body in a targeted manner, to create optimal conditions for the implementation of muscle activity.